2017
DOI: 10.18355/xl.2017.10.03.14
|View full text |Cite
|
Sign up to set email alerts
|

Gender identification in Russian written texts

Abstract: This article examines the identification of the gender of authors of Russian written texts using the quantitative parameters analysis approach. Identification of the gender of authors of texts is viewed as part of authorship profiling task. The material used for the study was a specially designed corpus of Russian texts "RusPersonality" which (along with other Slavic languages) has obtained little attention in authorship profiling studies. We made use of high-frequency text parameters occurring in texts of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…The best system ( Markov et al, 2017 ) reached only 68.25% accuracy in binary classification, and the organizers of the track hypothesised ( Litvinova et al, 2017b ) that the problem was that tweets are shorter and grammatically poorer in comparison with other sources ( e.g ., Facebook posts or essays). There were other studies on text-based gender detection that reported higher results, such as Sboev et al (2019) , which showed 0.62 accuracy on LiveJournal posts; Litvinova et al (2017a) achieved accuracy of 0.72 on tweets and 0.71 on Facebook posts; and Bogachev et al (2020) reported of 0.84 on RusPersonality ( Litvinova et al, 2016 ). Besides linguistic characteristics, some studies also considered information from user profiles as well as social graph.…”
Section: Appendixmentioning
confidence: 97%
“…The best system ( Markov et al, 2017 ) reached only 68.25% accuracy in binary classification, and the organizers of the track hypothesised ( Litvinova et al, 2017b ) that the problem was that tweets are shorter and grammatically poorer in comparison with other sources ( e.g ., Facebook posts or essays). There were other studies on text-based gender detection that reported higher results, such as Sboev et al (2019) , which showed 0.62 accuracy on LiveJournal posts; Litvinova et al (2017a) achieved accuracy of 0.72 on tweets and 0.71 on Facebook posts; and Bogachev et al (2020) reported of 0.84 on RusPersonality ( Litvinova et al, 2016 ). Besides linguistic characteristics, some studies also considered information from user profiles as well as social graph.…”
Section: Appendixmentioning
confidence: 97%
“…Вчені з усього світу вивчають ці зміни та їх наслідки у різних сферах людського життя. Дослідження в цих областях можуть допомогти розуміти, як інформаційні технології впливають на людську поведінку та допомогти розробляти стратегії, які максимально використовують позитивні наслідки інформаційних технологій, зменшуючи їхні негативні наслідки [4].…”
Section: Thought and Perception: Logical And Clip Thinking Of Future ...unclassified
“…The phrase "biometrics" may refer to a broad variety of various sorts of personal information, including but not limited to an individual's age, gender, and handedness, as well as other basic physical human traits that are unique to that person [1]. Research into the field of soft biometrics has exploded in recent years.…”
Section: Introductionmentioning
confidence: 99%